Self-efficacy in university faculty. - Landino, Rita A; Owen, Steven V (Journal of Vocational Behavior, 1988)
This study tested a causal model of academic self-efficacy in faculty at a large New England research university, focusing specifically on gender as one of 12 antecedent variables. Academic self-efficacy was defined as an estimate of confidence in one's ability to perform various tasks classified as research, service, and teaching in a university setting. The variables were drawn from Bandura's theory of self-efficacy and from characteristics of the university work setting. Data was obtained by mail response to a researcher-designed instrument: the Measure of Self-Efficacy in Academic Tasks (MSEAT). The findings show that being female contributed to feeling less efficacious about research tasks indirectly through the mediating influence of intervening variables. Feeling nourished and rewarded by a department and being male contributed to service self-efficacy. Teaching self-efficacy was not explained by the causal model. The implications of these findings are discussed in terms of campus socializing interventions, departmental research climate, and university incentives for female faculty. © 1988.
62 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/092-738-102-128-768 tex.type: [object Object]
Keywords: dept.csp